The TAB Battery Book: An In-Depth Guide to Construction, Design, and Use - Root Michael (Mc Graw Hill Higher Education, 2010)
Ideal for hobbyists and engineers alike, The TAB Battery Book: An In-Depth Guide to Construction Design and Use offers comprehensive coverage of these portable energy powerhouses. This practical guide discusses battery chemistry and engineering, how batteries are used, and the history of batteries. You'll find out how different types of batteries work and how to select the right battery for any application. The book also examines the technological advances being used to develop batteries as robust energy sources for a wide variety of devices. Tap into the power of all kinds of batteries with help from this detailed resource.